STUDY OF THE EROSIVE WEAR MECHANISM OF THE PIPELINE WALL - Марко, Тарас Іванович; Дорошенко, Ярослав Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The erosive wear basic mechanisms of the surface by solid particles, was studied. It was determined their influence on the metal surface. The formation mechanism schemes of erosion, was studied. The analysis of the factors, which distinguish the type of erosive wear, was carried out. It was determined that the most important factor of all are the velocity of the particles, impact angle and the intensity of the collision of particles with the wall of the pipeline, they are most often found in all models of erosive wear. The dependences of the erosive wear rate to the impact angle for plastic and brittle materials were determined. The effect of the temperature changes on the mechanism and rate of erosive wear, was studied. It was determined that with increasing of the temperature the material was plastic, therefore, the erosive rate will increase. The analysis of the impact of product flow regime to erosive wear of the pipe wall, was carried out. It was determined that the turbulent flow regime particles can repeatedly contact with surface. Instead, in laminar flow regime mainly particles moving with the flow and can go without damaging the surface, which reduces the erosive wear rate.